Komunikasi Keluarga dalam Membangun Motivasi Belajar Anak dibidang Olahraga Catur - Reni Fitriani; Siti Afifah Maulidia (Asosiasi Dosen Muda Indonesia, 2025)
Communication is a fundamental aspect of human life, as it is through this process that individuals can share information, build relationships, and understand the needs and meanings that arise in social interactions. Without communication, humans would struggle to collaborate, solve problems, and maintain the continuity of social life. Within the family environment, communication plays a significant role in children's growth and development. Through family interactions, children begin to understand the world around them, develop character, and develop self-confidence. This study focuses on how family communication patterns contribute to fostering children's motivation to learn in chess. The research approach used a qualitative method, with data collection techniques including in-depth interviews with three families with high-achieving chess children in Bogor Regency. The results indicate that democratic communication patterns are the most effective form of family communication in supporting children's emotional, social, and academic development. In the context of chess, parental support not only helps children improve technical skills but also fosters a positive, competitive mindset. The application of symbolic interaction theory also illustrates the relationship between the concepts of mind, self, and society, demonstrating how family communication patterns can strengthen children's motivation to learn and encourage the development of their potential in facing various challenges.